Transdiagnostic internet treatment for anxiety and depression: A randomised controlled trial - Titov, N.; Dear, B.; Schwencke, G.; Andrews, G.; Johnston, L.; Craske, M.; McEvoy, Peter (Elsevier, 2011)
Disorder-specific cognitive behavioural therapy programs delivered over the internet (iCBT) with clinicianguidance are effective at treating specific anxiety disorders and depression. The present study examined the efficacy of a transdiagnostic iCBT protocol to treat three anxiety disorders and/or depression within the same program (the Wellbeing Program). Seventy-seven individuals with a principaldiagnosis of major depression, generalised anxiety disorder, panic disorder, and/or social phobia wererandomly assigned to a Treatment or Waitlist Control group. Treatment consisted of CBT-based onlineeducational lessons and homework assignments, weekly email or telephone contact from a clinicalpsychologist, access to a moderated online discussion forum, and automated emails. Eighty one percent of Treatment group participants completed all 8 lessons within the 10 week program. Post-treatment data were collected from 34/37 Treatment group and 35/37 Control group participants, and 3-month follow-up data were collected from 32/37 Treatment group participants. Relative to Controls, Treatment group participants reported significantly reduced symptoms of anxiety and depression as measured by the Depression Anxiety and Stress Scales-21 item, Patient Health Questionnaire-9 item, and Generalised Anxiety Disorder-7 item scales, with corresponding between-groups effect sizes (Cohen’s d) at post treatment of .56, .58, and .52, respectively. The clinician spent a mean time of 84.76 min (SD ¼ 50.37) per person over the program. Participants rated the procedure as highly acceptable, and gains were sustained at follow-up. These results provide preliminary support for the efficacy of transdiagnostic iCBT in the treatment of anxiety and depressive disorders.